Age features of the thymocite RNA response in the thymus structural and functional areas to blood circulation disorders in the pool of carotic arteries in rats - Tkachuk, S.; Tkachuk, O.; Denysenko, O.; Yasinska, O.; Garvasiuk, O. (Journal of Education, Health and Sport, 2023)
Introduction. Ischemic-reperfusion injuries of the brain are accompanied by immunological disorders, which in their turn can extend post-ischemic changes in the brain. The studies of structural and functional changes in the thymus cells caused byischemia-reperfusion of the brain can supplement the existing understanding of the mechanism of the above interaction. The aim of the study. To investigate the reaction of thymocyte RNA in the structural and functional areas of the thymus gland to blood circulation disturbances in the carotid artery pool. Results. In rats of both age groups, cerebral ischemia-reperfusion reduces the content of RNA in the thymus cells in all the structural and functional areas of the thymus except the deep cortical one in one-month rats and the sub-capsular one in three-month rats. Conclusions. Acute circulatory disorders in the pool of the carotid arteries result in certain changes in RNA content in all the structural and functional areas of the thymus with age-related and structural features available.